Pharmacognostical phytochemical screening of andrographis paniculata (acanthaceae) - R.RAMASUBRAMANIA RAJA; P.SHANMUGA PANDIYAN (International Journal of Pharma and Bio Sciences, 2017)
Andrographis paniculata is a plant that has been effectively used in traditional Asian medicines for centuries. It’s perceived “blood purifying” property results in its use in diseases where blood “abnormalities” are considered causes of disease, such as skin eruptions, boils, scabies, and chronic undetermined fevers. A. paniculata has been reported as having antibacterial, antifungal, antiviral, choleretic, hypoglycemic, hypocholesterolemic, and adaptogenic effects. In the Unani system of medicine, it is considered aperients, anti-inflammatory, emollient, astringent, diuretic, emmenagogue, gastric and liver tonic, carminative, antihelmintic, and antipyretic..In present study was macroscopical, microscopy, physiochemical parameters (extractive values, crude fibre content , ash values, foreign organic matter), fluorescent analysis, plant cell inclusions reported. The ethanolic plant extraction was carried out by using soxhlet apparatus. The extract was screened for phytochemical properties by using colour reaction test.